Four battlegrounds : power in the age of artificial intelligence - Scharre, Paul (HighBridge Audio, 2023)
An award-winning defense expert tells the story of today's great power rivalry-the struggle to control artificial intelligence. A new industrial revolution has begun. Like mechanization or electricity before it, artificial intelligence will touch every aspect of our lives-and cause profound disruptions in the balance of global power, especially among the AI superpowers: China, the United States, and Europe. Autonomous weapons expert Paul Scharre takes listeners inside the fierce competition to develop and implement this game-changing technology and dominate the future. Four Battlegrounds argues that four key elements define this struggle: data, computing power, talent, and institutions. Data is a vital resource like coal or oil, but it must be collected and refined. Advanced computer chips are the essence of computing power-control over chip supply chains grants leverage over rivals. Talent is about people: which country attracts the best researchers and most advanced technology companies? The fourth "battlefield" is maybe the most critical: the ultimate global leader in AI will have institutions that effectively incorporate AI into their economy, society, and especially their military